2007
DOI: 10.1177/0091270006297748
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Rivastigmine Transdermal Patch Formulation in Healthy Volunteers: Relative Effects of Body Site Application

Abstract: A patch formulation of rivastigmine, an inhibitor of acetylcholinesterase and butyrylcholinesterase, is under development. The current objective was to evaluate the pharmacokinetic profile and patch adhesiveness following application at the upper back, chest, abdomen, thigh, and upper arm. In a single-dose, open-label, crossover study with 40 (42.5% men) healthy subjects, a 10-cm(2) patch containing 18 mg rivastigmine was applied to each body site. Median t(max) was 16 hours for all sites except the thigh (22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…However, in mild stages, and/or in cases when the caregiver is temporarily unavailable, patients would be able to apply their own patches. Although in the current study the patch was applied to the patient's upper back, pharmacokinetic studies have shown that it may also be applied to the upper arm or chest (Lefèvre et al, 2007), which may be more easily reached by the patient.…”
Section: Discussionmentioning
confidence: 95%
“…However, in mild stages, and/or in cases when the caregiver is temporarily unavailable, patients would be able to apply their own patches. Although in the current study the patch was applied to the patient's upper back, pharmacokinetic studies have shown that it may also be applied to the upper arm or chest (Lefèvre et al, 2007), which may be more easily reached by the patient.…”
Section: Discussionmentioning
confidence: 95%
“…The pharmacokinetics of rivastigmine 5, 10 and 15 cm 2 patches have been compared in three open-label trials: two single-dose studies involving either 39 healthy Caucasion or Japanese volunteers (mean age 25-27 years) [26] or 40 Caucasian volunteers (mean age 52 years) [27]; and a 14-day, multiple-dose study involving 51 patients with AD (mean age 71 years) [13]. The multiple-dose study also evaluated oral rivastigmine formulations [13].…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%
“…Absorption of rivastigmine from the patch is slow. Plasma rivastigmine concentrations are detectable 0.5-1 h following the first dose; after peaking at 8-16 h post-dose, plasma concentrations slowly decrease over the remainder of the 24-h application period [15,26,27]. Approximately half of the drug load is released from the patch during the 24-h application period [13,26] (see Sect.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%
“…No data are available on age's effect on extended-release formulations of dexmethylphenidate and methylphenidate pharmacokinetics. According to the label, age had no impact on the exposure to rivastigmine in AD patients [42,43].…”
Section: New Drug Formulationsmentioning
confidence: 99%